Do Democracies Tax Progressively? - Cantarelli, Luiz Guilherme Roth (2021)
The majority of studies that analyze the effects of democratization on inequality reduction dedicate limited attention to taxation and especially to tax progressivity. Taxes have the capacity of impacting significantly wealth and income distribution, being central mechanisms for inequality reduction. Measuring tax progressivity is a very complex task that has been explored by very few authors in political science. In this study, with tax data for 69 countries, I explore whether long term democratization has a significant and substantial impact on on the progressive structure of tax systems. To do so, I employ three measures of tax progressivity and the years that democracy has endured as the governing regime. I present a comparative time series analysis to show that long periods of democracy have only minor cumulative effects on tax progressivity.